Fabrications of hybrid zinc oxide nanorods -carbon nanotubes cotton - Md Yusof, Juraina; Ismail, Ismayadi; M. Yusop, Rahimi; Abdul Rashid, Suraya; Mohamed Ali, Mohamed Husham; Mat Nong, Mohd Ali; Osman, Rosiah (2018)
The preparation and characterization of zinc oxide (ZnO) nanostructures on green carbon nanotubes cotton (CNTC) was investigated. CNTC from waste cooking palm oil (WCPO) was synthesized via chemical vapor deposition (CVD) reactor. The CNTC is soft, fluffy, light weight and resembles cotton fiber used in textiles. ZnO nanostructures were grown on CNTC using chemical bath deposition method. It was observed that ZnO nanorods with aspect ratio of 9.32 of were successfully grown on the green CNTC. The combination of ZnO and CNTC hybrid is a promising composite that can be further explored in the application of electromagnetic absorbing material, piezoelectric nanogenerator and sensors.